2009
DOI: 10.1111/j.1439-0523.2008.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of QTLs for bread‐making quality in wheat using a recombinant inbred line population

Abstract: Whereas gluten fraction accounts for 30-60% of the variation in wheat bread-making quality, there remains substantial variation determined by non-gluten factors. The objective of this study was to detect new loci for wheat quality. The genetics of sodium dodecyl sulphate-sedimentation volume (Ssd), grain hardness (GH), grain protein content, wet gluten content (WGC) and water absorption (Abs) in a set of 198 recombinant inbred lines derived from two commercial varieties was studied by quantitative trait loci (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
99
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 32 publications
18
99
2
1
Order By: Relevance
“…Numerous studies have identified associations between HMW and LMW glutenin subunits and wheat quality (Payne 1987;Perretant et al 2000;Sourdille et al 2003;McCartney et al 2006;Nelson et al 2006;Zhang et al 2008;Li et al 2009;Mann et al 2009;Suprayogi et al 2009;Reif et al 2011;Li et al 2012;Echeverry-Solarte et al 2015). In this study, KN9204 and J411 differed at two HMW glutenin loci (Glu-A1 and Glu-B1) and two LMW glutenin loci (Glu-A3 and Glu-B3).…”
Section: Novel Stable Qtls and Qtl Co-segregation With Known Genesmentioning
confidence: 86%
See 2 more Smart Citations
“…Numerous studies have identified associations between HMW and LMW glutenin subunits and wheat quality (Payne 1987;Perretant et al 2000;Sourdille et al 2003;McCartney et al 2006;Nelson et al 2006;Zhang et al 2008;Li et al 2009;Mann et al 2009;Suprayogi et al 2009;Reif et al 2011;Li et al 2012;Echeverry-Solarte et al 2015). In this study, KN9204 and J411 differed at two HMW glutenin loci (Glu-A1 and Glu-B1) and two LMW glutenin loci (Glu-A3 and Glu-B3).…”
Section: Novel Stable Qtls and Qtl Co-segregation With Known Genesmentioning
confidence: 86%
“…The measurements were calibrated using calibration samples according to the manufacturer's instructions. Previous studies have confirmed that NIRS is a powerful method for measuring the quality traits of wheat; that it is rapid, effective, and convenient compared with traditional methods; and that it is appropriate for use in wheat breeding programs designed to improve quality-related traits (Sourdille et al 1996;Perretant et al 2000;Turner et al 2004;Kuchel et al 2006;Nelson et al 2006;Li et al 2009Li et al , 2012Mann et al 2009;Suprayogi et al 2009;Sun et al 2010;Asif et al 2015).…”
Section: Plant Materials Experimental Design and Phenotypic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In wheat, QTLs have been mapped for many quality traits such as grain protein content (Blanco et al, 2002;Campbell et al, 2001;Groos et al, 2003;Joppa et al, 1997;Sourdille et al, 2003;Suprayogui et al, 2009;Turner et al, 2004;Zanetti et al, 2001), grain hardness (Sourdille et al, 2003;Turner et al, 2004;Zanetti et al, 2001), and dough quality traits such as mixing time, mixing tolerance, dough tenacity and dough extensibility (Campbell et al, 2001;Cornish et al, 2001;Crepieux et al, 2005;Elangovan et al, 2008;Huang et al, 2006;Li et al, 2009;Ma et al, 2007;Mann et al, 2009;Nelson et al, 2006;Patil et al, 2009;Perretant et al, 2000;Sourdille et al, 2003;Zanetti et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…markgrafii defined by the microsatellite loci Xgwm148, Xgwm374 and Xgwm972 in 2B chromosome may be the donor of high gluten content in grain as well. In the mapping population Neixiang 188 × Yanzhan 1, Li et al (2009) revealed the associated QTL in the region of the molecular marker Xbarc55 which is positioned only in 2.4 cM from Xgwm374 (GRAINGENES Database, http://wheat.pw.usda.gov). Small introgression in 3BL chromosome was only indicated by one microsatellite marker Xgwm1005 ) and was positioned between the markers Xgwm108 and Xgwm112.…”
Section: Discussionmentioning
confidence: 99%